Taylor‐Couette reactor: Principles, design, and applications. Issue 5 (22nd February 2021) - Schrimpf, Marco; Esteban, Jesús; Warmeling, Helge; Färber, Tobias; Behr, Arno; Vorholt, Andreas J.
Abstract: The Taylor‐Couette reactor (TCR) is an apparatus that capitalizes on the Taylor‐Couette flow, which allows many flow regimes and conditions to perform (bio‐)chemical conversions with precise control of various reactor characteristics. With the possibility to continuously perfuse the reactor with a reaction medium, the TCR becomes interesting for chemical engineering applications. In this review, we introduce this reactor type and provide an overview of its history, principles of the flow regimes, and a description and design aspects of the reactors and their elements. Available information in the literature is summarized and harmonized to present available formulas and correlations in a consistent set of variables. Additionally, a wide number of applications in process technology are covered, including reactions in homogeneous, photo, and enzymatic catalysis, polymer synthesis, and crystallization and aggregation‐flocculation processes. Focusing on this reactor configuration, this article intends to be used as a hub for scientific groups interested in TCRs.